Pendidikan Karakter di Madrasah Ibtidaiyah Modern Sahid, Bogor, Jawa Barat - Sumarsih Anwar (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2014)
This study aims to know (1) opinion and policy of principal of Sahid Modern Madrasah Bogor on character education (2) implementation of character education in Sahid Modern MI Bogor and (3) evaluation and assessment of character values. This study is a case study done at Sahid Modern MI Bogor, West Java using qualitative approach. The main instruments are interview, observation technique and documented study. The findings are (1) Principal of Sahid Modern MI Bogor believes that Islam already had a more comprehensive term than character education namely akhlakul karimah (good moral). Madrasah is not only responsible in producing students that excel in science and technology but also Islamic character and personality. (2) Character education is done by integrating values of character in every subject, intra curriculum and extra curriculum subject andculture development and (4) evaluation and assessment of attitude and behavior (values of akhlakul karimah) is done by teacher by observing the students at school when students are at school.